SCIENTIFIC CONCEPTS OF SPEED AND STRENGTH TRAINING OF ATHLETES IN THE TRIPLE JUMP 14-15 YEARS OLD IN ATHLETICS - Павленко, Віктор (SWorldJournal, 2026)
The problem of the level of general physical fitness at the stage of basic training of triple jumper athletes aged 14-15 deserves attention in the systematization of the training process. Substantiating the relevance of the study of speed and strength fit